Pengaruh Inovasi Produk dan Pemasaran Digital terhadap Keunggulan Bersaing UMKM di Era Digital - Fadali Rahman; Siti Nikmatus Salamah; Syarina Jazilatul Mukarromah; Aulia Ramadhani Fauzia; Rohmaniyah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of product innovation and digital marketing on the competitive advantage of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. Product innovation and digital marketing are considered important factors in increasing the competitiveness of MSMEs in an increasingly competitive market. This study uses a quantitative method with a survey of MSMEs in Sampang. The data were analyzed using multiple regression techniques to test hypotheses. The results of the study show that product innovation and digital marketing have a significant positive effect on the competitive advantage of MSMEs. Product innovation allows MSMEs to offer products that are more attractive and relevant to consumers, while digital marketing expands market reach and increases the effectiveness of promotions. This research provides practical implications for MSMEs to continue to innovate and utilize digital technology in their marketing strategies to achieve a lasting competitive advantagejutan.